Impact of Dispersity and Hydrogen Bonding on the Lubricity of Poly(acrylamide) Brushes. Issue 14 (27th May 2019) - Mandal, Joydeb; Simic, Rok; Spencer, Nicholas D.
Abstract: The effects of chain‐length dispersity and monomer type on the lubricity of acrylamide‐based polymer brushes have been examined in aqueous media. The polymer brushes used have been synthesized by surface‐initiated, atom‐transfer radical polymerization of N, N ‐dimethylacrylamide (DMAM), N ‐hydroxyethyl acrylamide (HEAM), and N ‐isopropylacrylamide. Polymerization reactions have been performed in the presence and also in the absence of CuX2 and tEtAmX (X = Cl or Br), in order to achieve polymer brushes with substantial differences in their chain‐length dispersities. While an influence of the dispersity on the lubricity of the polymer brushes can be observed, it is convoluted with the competing phenomena of hydrogen bonding and increased water content. The most hydrophilic, p(HEAM) brush exhibits the highest friction coefficient (μ) of ≈0.04 compared to ≈0.004 in the case of the p(DMAM) brush. Such a large difference is presumed to originate from the hydrogen bonding between the tribological countersurface (plasma‐oxidized poly(dimethylsiloxane)) and the p(HEAM) chains, as evidenced by the substantial reduction in μ when the friction measurements are performed in 5m urea solution instead of pure milli‐Q water. Abstract : Hydrogen bonding between the monomer units, water molecules, and the countersurface appears to be critical in determining the complex lubrication behavior of polyacrylamide brushes in water, as evidenced by the dramatic effects of urea addition. H‐bond tailoring is an important new consideration in the design of new polymer‐brush‐based systems for efficient aqueous lubrication.